(untitled) (Proceedings of the Global Public Health Conference, 2023)
Studies found that in low-middle-income countries, many people changed their lifestyle into a modern and industrialized lifestyle. Eating habits inevitably induced by personal food choice which has an independent effect on health. Establishment of eating habits and preferences mostly occurred in young age. Eating habits during adolescence period may sustain until adulthood with consequences for long-term health problem. This project aims to develop community-based intervention programme to tackle this adolescent food choice problem, and examine the effectiveness of a selected method in a sub-urban area in Serang district, Banten, Indonesia. A research on factors that drive food choice motives on adolescents was conducted through a focus group discussion, analysed by thematic analysis. Intervention program recommendation was then formulated by intervention mapping method. To examine the effectiveness of nudging application in minimarket, an experiment with customer acceptance and shopping motives survey was executed and analysed by SPSS. The results of the research show that behaviour of target groups is determined mostly by low self-regulation, family and peer influence, and limited food preparation time. Some intervention recommendations were developed to address these determinants, e.g. family-based intervention, peer-led intervention, and school collaboration. Culturally-sensitive learning environments could also be examined to ensure the effectiveness of nutrition education in that area. Nudging as one of assumed appropriate method to tackle an impulsive behaviour seemed to be not effective in increasing healthy product sales (p=0,741; p=0,316; p=0,342; p=0,247) but the customers showed a positive attitude towards its future application